The effect of teaching approaches and curriculum designs in reducing mathematics anxiety—a literature review - Ma, Yu Fei (Frontiers in Education, 2025)
In recent years, reducing students’ mathematics anxiety has become an objective to improve teaching quality and reduce academic stress. Mathematics anxiety is the feeling of tension or fear when students are dealing with mathematical tasks. These negative emotions may hinder students’ learning efficiency and lead to lower academic achievement. This mini-review aims to analyze the roles of teaching approaches and curriculum designs in reducing mathematics anxiety. Furthermore, this mini-review followed the PRISMA guidelines and screened 35 relevant literature sources from Google Scholar, Web of Science, and Scopus for data analysis. According to the analysis, teachers use flat teaching and the REACT model to promote students’ engagement and confidence. Specifically, REACT is an acronym for relating, experiencing, applying, cooperating, and transferring. In contrast, teachers should design application-oriented and experiential curriculums to connect mathematics with real-world contexts through practical exercises. By reading this mini-review, teachers can better understand the concept of mathematics anxiety and its impact on students’ learning. Peer researchers can also identity the limitations of the literature in this area.